Molecular interactions at the bovine embryo–endometrial epithelium interface. Issue 6 (December 2020) - Sponchiado, Mariana; Marei, Waleed F A; Beemster, Gerrit T S; Bols, Peter E J; Binelli, Mario; Leroy, Jo L M R
Abstract : In cattle, pre-implantation embryo development occurs within the confinement of the uterine lumen. Current understanding of the bi-lateral molecular interactions between embryo and endometrium that are required for a successful pregnancy is limited. We hypothesized that the nature and intensity of reciprocal embryo-endometrium interactions depend on the extent of their physical proximity. Bovine endometrial epithelial cells (bEECs) and morulae were co-cultured in juxtacrine (Contact+) or non-juxtacrine (Contact−) apposition. Co-culture with bEECs improved blastocyst rates on day 7.5, regardless of juxtaposition. Contact+ regulated transcription of 1797 endometrial genes vs only 230 in the Contact− group compared to their control (no embryos) counterparts. A subset of 50 overlapping differentially expressed genes (DEGs) defined embryo-induced effects on bEEC transcriptome irrespective of juxtaposition. Functional analysis revealed pathways associated with interferon signaling and prostanoid biosynthesis. A total of 175 genes displayed a graded expression level depending on Contact+ or Contact−. These genes were involved in interferon-related and antigen presentation pathways. Biological processes enriched exclusively in Contact+ included regulation of cell cycle and sex-steroid biosynthesis. We speculate that, in vivo, embryonic signals fine-tune the function of surrounding cells to ultimately maximize pregnancy success.